2020
DOI: 10.3390/genes11040354
|View full text |Cite|
|
Sign up to set email alerts
|

Study of the Association between microRNA (miR-25T>C, miR-32C>A, miR-125C>T, and miR-222G>T) Polymorphisms and the Risk of Recurrent Pregnancy Loss in Korean Women

Abstract: Recurrent pregnancy loss (RPL), which is defined as two pregnancy losses that occur before 20 weeks of gestation, is relatively common, occurring in approximately 1–5% of women. The underlying cause is often unclear, although numerous factors may contribute to RPL, including environmental and immunological factors, blood coagulation disorders, and genetics. In particular, single nucleotide variants have been associated with RPL, including those found in microRNAs (miRNAs). We investigated the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Moreover, environmental factors such as infection, smoking, alcohol, psychological trauma, and stress may contribute to RPL [ 8 , 9 , 10 ]. However, the cause of RPL is unclear in 30–40% of cases, and recent studies suggest that genetic factors play an important role in the pathogenesis of idiopathic RPL [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, environmental factors such as infection, smoking, alcohol, psychological trauma, and stress may contribute to RPL [ 8 , 9 , 10 ]. However, the cause of RPL is unclear in 30–40% of cases, and recent studies suggest that genetic factors play an important role in the pathogenesis of idiopathic RPL [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional findings revealed the involvement of miR‐326 in intrauterine adhesion, leading to infertility and pregnancy loss, here it was deciphered that the said miRNA negatively regulates the TGF‐β1/Smad3 pathway by targeting TGF‐β1, suggesting its vital role as a prognostic marker and as a therapeutic target (Ning et al, 2018). Furthermore, structural changes, such as nucleotide polymorphisms in miRNAs, can also lead to pregnancy loss by modulating target selection that impacts pregnancy outcomes influencing proliferation, invasion, migration, and embryonic development pathways (Jeon et al, 2012; Lee et al, 2020; X. Q. Wang, Li, et al, 2018). However, only a handful of studies have shown dysregulated expression of lncRNAs responsible for URPL by altering numerous biological pathways, among which the majority are inflammatory and infection pathways genes (Z. Huang, Du, et al, 2018; Wang et al, 2014).…”
Section: Ncrnas In Women's Healthmentioning
confidence: 99%
“…Currently, a clinical need exists for predictive biomarkers of pregnancy complications, such as RPL [75]. The number of NK cells has already become a clinical reference index for RPL [76], and several circulating miRNAs are also known to be differentially expressed in RPL patients when compared with healthy individuals, acting as potential biomarker candidates [77,78]. But whether differentially expressed miRNAs in NK cells can be able to more accurately discern normal individuals from those with pregnancy related disorders should be revealed in more in-depth studies.…”
Section: Future Directionsmentioning
confidence: 99%